ANALISIS HAMBATAN DAN GERAKAN ROLLING TERHADAP VARIASI SUDUT DAN NACA SEBAGAI FIN STABILIZER PADA KAPAL PESIAR - Bagas Adisetyantoko (2023)
Cruise ships are a type of vessel used for leisure travel. To improve efficiency and comfort, the cruise ship industry has incorporated several advanced technologies, such as environmentally friendly fuel utilization and enhanced ship design to reduce friction. However, the installation of fin stabilizers on ships poses challenges. The unique shape of stabilizers compared to other parts of the ship alters the water flow around the vessel, increasing resistance. This study focuses on the resistance and rolling motion of ships using fin stabilizers with various angles and NACA profiles. Computational Fluid Dynamics (CFD) simulations were conducted using Ansys CFD software for resistance analysis and Maxsurf Motion for seakeeping analysis. The results reveal that NACA 0015 and 0012 profiles can decrease average resistance by 7.02% compared to previous research using NACA 0021. At a 30˚ angle, resistance increases by 64.82% compared to the 0˚ angle. Among the various NACA profiles studied, NACA 0015 at a 0˚ angle provides the optimal value for reducing rolling motion. Thus, this research indicates that a fin stabilizer with a 0˚ angle of inclination is the most efficient in minimizing resistance and rolling motion of cruise ships.